One-pot synthesis of lignin-based electrospun oxygen reduction reaction electrocatalysts - Ruiz-Rosas, Ramiro Rafael; García-Mateos, Francisco José; Cordero-Alcántara, Tomás; Rodríguez-Mirasol, José; Ortega, Alejandro; Cazorla-Amorós, Diego; Morallón, Emilia (My University, 2018)
Owing to their adequate combination of high surface area, electrical conductivity and electrochemical resistance, carbon fibers has been used for a long time as a catalyst supports and gas diffusion layers in the electrodes of fuel cells. However, the use of high amounts of noble metals in the cathode is hampering the commercial utilization of fuel cells. We have recently demonstrated that the electrospinning of lignin, a widely available and non-expensive biopolymer, allows the production of porous carbon cloths, which have been already utilized as electrodes for methanol oxidation and supercapacitors. In this work, we propose the electrospinning of lignin and noble/non-noble metal precursors for one-pot production of ORR catalysts. Fe, Co, Pd and Pt salts have been incorporated onto lignin-ethanol solutions and have been electrospun in microsized, metal-decorated lignin fibers. The stabilization and carbonization of these fibers have produced carbon electrodes with supported metallic nanoparticles up to 10 % wt. loading, avoiding the use of further impregnation steps. In addition, the incorporation of metal precursors in the lignin solution enhances the development of mesoporosity in the resulting carbon fibers, a desirable feature for increasing mass transfer rate when used as electrocatalyst, without compromising their electrical conductivity. The electrochemical characterization has confirmed that these carbon cloths are promising ORR catalysts that could be useful for the reducing the amount of noble metals in the electrodes or for allowing the use of non-noble metals as catalysts.
Keywords: Carbón - Congresos; Lignina; ORR; Fibras; Catalizador; Electroquímica; Platino; Hierro; Cobalto; Paladio; Pilas de combustible